Gideon the cutpurse - Buckley-Archer, Linda (New York Simon & Schuster Books for Young Readers, 2006)
Ignored by his father and sent to Derbyshire for the weekend, twelve-year-old Peter and his new friend, Kate, are accidentally transported back in time to 1763 England where they are befriended by a reformed cutpurse.
Birthday treat -- Peter misses an important telephone call -- Three-cornered hat -- Howl of a wolf -- Breakfast of grilled trout -- Lost in time -- Hospitality of the honorable Mrs. Byng -- Tar man's tale -- Journey begins -- Attack! -- Lord Luxon's tragedy -- Parliament of rocks -- Pandora's box -- Gideon's stratagem -- Pact made in blood -- Two covent gardens -- Queen Charlotte's promise -- Into the net -- Race against time -- Newgate -- Straw men -- Tyburn -- Author's note -- Acknowledgments.
Sequel: The time thief.
Illustration on endpapers.
010 up.
Middle School.
Accelerated Reader AR
Reading Counts
Keywords: 1760-1820; Time travel -- Juvenile fiction; Brigands and robbers -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Fantasy fiction -- Juvenile fiction; Robbers and outlaws -- Fiction; Thieves -- Fiction; Father-son relationship -- Fiction; Great Britain -- History -- George III, 1760-1820 -- Juvenile fiction; Young adult fiction; Time travel (Fiction); Domestic fiction; Fantasy fiction; History; Science fiction